Comparison of 2.5% agarose gel vs hyaluronic acid filler, for the correction of moderate to severe nasolabial folds - Scuderi, Nicolò (J Cosmet Dermatol, 2021)
BACKGROUND: Agarose gel filler is a natural hydrocolloid with a three‐dimensional structure similar to the extracellular matrix, with gel formed by hydrogen bonds and electrostatic interactions rather than through chemical cross‐linking or polymerization. OBJECTIVE: To determine efficacy and safety of 2.5% agarose gel filler for the correction of nasolabial folds. METHODS: In this split‐face study, efficacy, safety, and usability of 2.5% agarose gel were compared to those of NASHA‐L. Assessments included the nasolabial fold (NLF) Wrinkle Severity Rating Scale (WSRS), Global Aesthetic Improvement Scale (GAIS [blinded investigator]), subject satisfaction, safety (adverse events), and usability. RESULTS: Sixty‐six subjects were treated, and 46/66 (66.7%) were available for evaluation at 3 months, when mean change in WSRS was identical for both products (−1.1 ± 0.4 for 2.5% agarose; −1.1 ± 0.4 for NASHA‐L). Scores for each product remained similar across all time points and began to return to baseline between 7 and 8 months. GAIS score followed a similar pattern, rising between months 7 and 8 (2.7 ± 0.6 for 2.5% agarose at month 7‐3.3 ± 0.5 at month 8 and 2.7 ± 0.6 for NASHA‐L at month 7‐3.3 ± 0.5 at month 8). Ultrasound confirmed the longevity of both fillers between 7 and 8 months. All adverse events were transient in nature and resolved within 15 days. Most events were mild in nature, and the number of events was similar between the two fillers. CONCLUSION: Treatment with 2.5% agarose gel resulted in improvement that persisted for between 7 and 8 months. The treatment effect was equivalent to NASHA‐L.